2020
DOI: 10.1007/s10964-020-01212-2
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Examination of Links between Parent–Adolescent Communication and Adolescent Psychological Problems in 12 Cultural Groups

Abstract: Internalizing and externalizing problems increase during adolescence. However, these problems may be mitigated by adequate parenting, including effective parent-adolescent communication. The ways in which parent-driven (i.e., parent behavior control and solicitation) and adolescent-driven (i.e., disclosure and secrecy) communication efforts are linked to adolescent psychological problems universally and cross-culturally is a question that needs more empirical investigation. The current study used a sample of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 61 publications
3
37
0
Order By: Relevance
“…Corroborating results from other studies, we found that adolescent disclosure was linked to less adolescent emotional problems (Fernandez et al 2018 ) and delinquency (Kapetanovic et al 2019a ) over time, while adolescent secrecy was linked to more emotional and conduct problems (Kapetanovic et al 2020 ), delinquency (Frijns et al 2010 ), and poorer wellbeing (Elsharnouby and Dost-Gözkan 2020 ) over time. In addition, higher levels of adolescent emotional problems predicted less disclosure over time, demonstrating the reciprocal nature of these links.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Corroborating results from other studies, we found that adolescent disclosure was linked to less adolescent emotional problems (Fernandez et al 2018 ) and delinquency (Kapetanovic et al 2019a ) over time, while adolescent secrecy was linked to more emotional and conduct problems (Kapetanovic et al 2020 ), delinquency (Frijns et al 2010 ), and poorer wellbeing (Elsharnouby and Dost-Gözkan 2020 ) over time. In addition, higher levels of adolescent emotional problems predicted less disclosure over time, demonstrating the reciprocal nature of these links.…”
Section: Discussionsupporting
confidence: 85%
“…The measure frequently used in studies on parent-adolescent communication (e.g. Frijns et al 2010;Kapetanovic et al 2020) come from Stattin and Kerr (2000). Parental behavioral control assessed ways in which parents set rules and regulations to control and regulate adolescents' behavior.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, when adolescents feel emotionally close to their parents (Tilton-Weaver et al 2010) they tend voluntarily to share information about their everyday activities with their parents, which gives parents the possibility to give their adolescents support and guidance without being perceived as intrusive. Although studies show support for the protective role of parent-driven communication efforts in terms of adolescent psychological health (Pinquart 2017a(Pinquart , 2017b, adolescent disclosure seems to be the strongest protective predictor of adolescent psychological health, including adolescent depressive symptoms (Hamza and Willoughby 2011) and the externalizing of problems (Kapetanovic et al 2020). In other words, in order for parents to provide beneficial guidance for adolescents they need to have knowledge of adolescent whereabouts and to communicate with their adolescents.…”
Section: Parenting Adolescentsmentioning
confidence: 99%